Studi Penilaian Ekosistem Mangrove Hasil Tanam Berdasarkan Keberadaan Gastropoda di Pulau Pramuka, Kepulauan Seribu, Jakarta - Assuyuti, Yayan Mardiansyah; Rijaluddin, Alfan Farhan (Journal of Marine and Aquatic Sciences, 2016)
The aims of mangrove replanted are to protect and good quality of coastal ecosystems and small islands, but it is have influenced to change of habitat and ecology function. This study conducted at Pramuka Island, Seribu islands, Jakarta, in June 2016. Data of gastropoda using 1 m 2 square random sampling and divide depend on height are 0-1, 1-2 and 2-3 m. The aims of study are to determine (i) diversity, density, (ii) vertical distribution, (iii) size shell, (iv) correlation of density with distribution, (v) correlation of size shell with vertical distribution, (vi) correlation of individual with height gastropoda, and (vii) assessment of mangrove replanted depend on gastropoda. The species of Terebralia sp. and Littorina sp. are found in mangrove replanted. The total value of diversity and density of mangrove gastropoda are 0.6 and 31.3 ind/m 2 , respectively. Vertical distribution of gastropoda Terebralia sp. found in 0-1 m and Littorina sp. in 0-3 m. The density and individual of Terebralia sp. have high value and size shell largest than Littorina sp. Gastropoda found indicated that the mangrove ecosystem in Pramuka island is still young and is in a transition state.
Keywords: Mangrove; Pramuka island; Diversity; Density; Vertical Distribution